Impact of APOE Alleles-by-Diet Interactions on Glycemic and Lipid Features– A Cross-Sectional Study of a Cohort of Type 2 Diabetes Patients from Western Mexico: Implications for Personalized Medicine - Torres-Valadez R; Ramos-Lopez O; Frías Delgadillo KJ; Flores-García A; Rojas Carrillo E; Aguiar-García P; Bernal Pérez JA; Martinez-Lopez E; Martínez JA; Zepeda-Carrillo EA (Dove Medical Press, 2020)
Rafael Torres-Valadez,1,2,* Omar Ramos-Lopez,3,* Kevin J Frías Delgadillo,1 Aurelio Flores-García,1 Esaú Rojas Carrillo,4 Pedro Aguiar-García,1 J Antonio Bernal Pérez,4 Erika Martinez-Lopez,5 J Alfredo Martínez,6,7 Eloy A Zepeda-Carrillo1,8 1Specialized Unit in Research, Development and Innovation in Genomic Medicine, Nayarit Center for Innovation and Technology Transfer, Autonomous University of Nayarit, Tepic, Nayarit, Mexico; 2Integral Health Academic Unit, Autonomous University of Nayarit, Tepic, Nayarit, Mexico; 3Faculty of Medicine and Psychology, Autonomous University of Baja California, Tijuana, Baja California, Mexico; 4Family Medicine Unit No. 24 “Ignacio García Tellez”, Mexican Social Security Institute, Tepic, Nayarit, Mexico; 5Institute of Translational Nutrigenetics and Nutrigenomics, Department of Molecular and Genomic Biology, University Center of Health Sciences, University of Guadalajara, Guadalajara, Jalisco, Mexico; 6Precision Nutrition and Cardiometabolic Health, IMDEA-Food Institute (Madrid Institute for Advanced Studies), Madrid, Spain; 7CIBERobn, Fisiopatología De La Obesidad y La Nutrición, Carlos III Health Institute, Madrid, Spain; 8Tepic Civil Hospital “Dr. Antonio González Guevara”, Health Services in Nayarit, Tepic, Nayarit, Mexico*These authors contributed equally to this workCorrespondence: Eloy A Zepeda-CarrilloNayarit Center for Innovation and Technology Transfer, Autonomous University of Nayarit, Calle Tres S/N, Ciudad Industrial, Tepic, Nayarit 63117, MéxicoTel +52-3112487861Email eloyz@uan.edu.mxPurpose: To analyze clinically relevant interactions between the apolipoprotein E (APOE) ϵ2, ϵ3 and ϵ4 alleles and nutritional factors on glycemic control and lipid levels in a cohort of type 2 diabetes (T2D) patients from western Mexico.Patients and Methods: In this cross-sectional study of the cohort of T2D patients, a total of 224 individuals were selected for interaction studies. Clinical and anthropometric data were obtained from pre-designed medical records. Dietary intake was assessed by validated three-day food consumption records. Biochemical measurements were determined by automated methods. APOE genotyping was performed by a real-time allelic discrimination assay. Gene–diet interactions were tested by corrected multiple linear regression analyses, which were adjusted by potential confounding factors such as age, sex, energy intake, BMI and anti-hyperglycemic therapy (Metformin, Glibenclamide or Insulin), and years with T2D.Results: Seventy-six percent of patients with T2D were on Metformin therapy. The frequencies of the APOE alleles were ϵ2 (5.8%), ϵ3 (74.1%) and ϵ4 (20.1%). After statistical settings, significant APOE alleles-by-diet interactions in relation to the metabolic profile were found. Interestingly, higher blood levels of total cholesterol (p int. = 0.016), non-HDL-c (p int. = 0.024), and LDL-c (p int. = 0.030) were found only in carriers of the APOE ϵ2 allele with a low consumption of MUFA. In contrast, carriers of the APOE ϵ4 allele with a high ω-6:ω-3 PUFA ratio in the diet had higher %HbA1c blood concentrations (p int. = 0.035).Conclusion: This study suggests a differential metabolic impact of APOE alleles on lipid/glycemic phenotypes depending on the dietary intake, with important potential implications in the personalized medicine and nutritional management of patients with type 2 diabetes mellitus.Keywords: type 2 diabetes, APOE alleles, glycemic control, ω-6:ω-3 PUFA ratio, personalized medicine, gene–nutrient interactions